2017
DOI: 10.1159/000470822
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-9 Inhibits NLRP3 Inflammasome Activation in Human Atherosclerosis Inflammation Cell Models through the JAK1/STAT Signaling Pathway

Abstract: Background/Aims: MicroRNA-9 (miR-9) is involved in inflammatory reaction in atherosclerosis; however, its function and regulatory mechanisms remain unclear. We aimed to uncover the exact roles of miR-9 and downstream signaling pathways using in vitro human atherosclerosis models. Methods: We used oxidized low-density lipoprotein (oxLDL)-stimulated human THP-1 derived macrophages, oxLDL-stimulated human primary peripheral blood monocytes and lipopolysaccharides (LPS) or Alum-stimulated human THP-1 derived macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 55 publications
5
73
0
Order By: Relevance
“…miR‐134 promotes AS development via the ANGPTL4/LPL pathway in apolipoprotein E knockout mice . miR‐9 represses NLRP3 inflammasome activation in AS inflammation cell models through the JAK1/STAT pathway . Numerous studies have reported that miR‐128 is involved in different cellular processes including differentiation, apoptosis and metabolism .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐134 promotes AS development via the ANGPTL4/LPL pathway in apolipoprotein E knockout mice . miR‐9 represses NLRP3 inflammasome activation in AS inflammation cell models through the JAK1/STAT pathway . Numerous studies have reported that miR‐128 is involved in different cellular processes including differentiation, apoptosis and metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…NEAT1 can contribute to hepatocellular carcinoma development through sponging miR‐485 and activating STAT3 . Knockdown of NEAT1 inhibits osteosarcoma progression by sponging miR‐194 …”
Section: Introductionmentioning
confidence: 99%
“…Chronic vascular inflammation is closely related to AS development [36]. Previous studies have revealed that apigenin can protect against inflammation [22,23].…”
Section: Apigenin Inhibits the Activation Of Tlr-4/nf-κb Pathway In Mmentioning
confidence: 99%
“…NLRP3 inflammasome is assembled by NLRP3, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), caspase-1 released after an endogenous ‘‘danger signal” and exogenous infection, comprise an important cytosolic protein complex [34]; this provides a caspase-1-activation platform to promote the maturation and release of proinflammatory cytokines, including IL-1β and IL-18 [35]. NLRP3 inflammasome plays a critical role in lung injury in diverse models [34, 36].…”
Section: Discussionmentioning
confidence: 99%